2018
DOI: 10.2174/1874149501812010401
|View full text |Cite
|
Sign up to set email alerts
|

Study of a New Plaster Composite Based on Dune Sand and Expanded Polystyrene as Aggregates

Abstract: Introduction:This study aims to highlight the physicomechanical properties of a new lightweight construction material which is composed of plaster as a binder and dune sand and Expanded Polystyrene Beads (EPS) as aggregates.Methods:For this purpose, different mixtures were designed with different percentages and particle sizes of EPS aggregates in order to test the porosity, the density and the thermo-mechanical properties of the studied composite. Furthermore, Electron Microscopy (EM) visualisation and SEM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…These results are in line with those reported by Laoubi et al [19], with regard to the thermal conductivity of plaster composite containing Expanded Polystyrene (EPS) and dune sand as aggregates. The authors found the values of thermal conductivity ranging from 0.75 to 0.2 W/mK as the content of EPS increased from 0 to 50% (Fig.…”
Section: Thermal Characterization Of the Mortar Specimenssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in line with those reported by Laoubi et al [19], with regard to the thermal conductivity of plaster composite containing Expanded Polystyrene (EPS) and dune sand as aggregates. The authors found the values of thermal conductivity ranging from 0.75 to 0.2 W/mK as the content of EPS increased from 0 to 50% (Fig.…”
Section: Thermal Characterization Of the Mortar Specimenssupporting
confidence: 93%
“…Otherwise, as expected, the porosity increases with the increase of the AEA; once again a variation in the gradient is observed for AEA of 0.05%. These results can be compared with the research by Laoubi et al [19], who determined the compressive and flexural strengths of a lightweight construction material composed of plaster as a binder and dune sand and Expanded Polystyrene Beads (EPS) as aggregates. According to the proportion and sizes of particles of EPS, the authors found a mean compressive and flexural strength of about 2.8 and 1.5 MPa respectively, in correspondence with the percentage of EPS content of 50%.…”
Section: Mechanical Characterization Of the Mortar Specimensmentioning
confidence: 87%
See 1 more Smart Citation
“…This decrease in density can be considered the first positive characteristic of natural fibers, as lightweight building materials are greatly encouraged in modern engineering. This phenomenon is always taking place on composite with plaster and vegetable fibers according to several works such as Laoubi et al [17], and Ochang et al [18].…”
Section: Physical Propertiesmentioning
confidence: 99%
“…These results can be explained, on the one hand, by the fact that the palm fibers had lower thermal conductivity than plaster. In this sense, several researchers have used this argument to explain the decrease in thermal conductivity of the plaster reinforced with natural fibers [17]. Moreover, on the other hand, other researchers have also attributed this behavior to the voids entrapped between the palm fibers and the plaster, due to the weak adhesion between the fibers and the matrix and to poor samples preparation, which creates closed porosity zones, thus increasing the insulation aspect of the material.…”
Section: Thermal Propertiesmentioning
confidence: 99%